Colour image dehazing using near‐infrared fusion. Issue 8 (13th July 2017) - Jang, Dong‐Won; Park, Rae‐Hong
Abstract : This study proposes a colour image dehazing method using a near‐infrared (NIR) image. Haze is a degradation in colour images caused by light scattering and is dependent on the wavelength of the light and the size of atmospheric particles. According to Rayleigh's law, an NIR image is less scattered than a red‐green‐blue (RGB) image, and in this study, it is observed that in a small patch of a haze‐free image, the high‐frequency (HF) components of the RGB and NIR images are similar to each other; in contrast, those in a small patch of a hazy image are different from each other. This study proposes a new dehazing method that fuses the HF components of the RGB and NIR images in a local hazy patch; the HF components in the patch are then used to generate the weight maps used to combine detail layers. The proposed method enhances the detail layer of a hazy RGB image by fusing the detail layers of the RGB and NIR images, while the base layer is restored using an existing single image dehazing method. Experimental results show that the proposed method is qualitatively better than existing methods.